Using life-history information to identify management priorities within an emergent multi-species grey mullet fishery - Calum J. Pritchard; Ayşegül Tuğçe Han; Andrew Macleod; Rachel M. Turnbull; Jamie Small; Sarah Birchenough; Simon Pengelly; Benjamin J. Ciotti (Fisheries Research, 2026)

Genetic composition and conservation status of coastal cutthroat trout (Oncorhynchus clarki clarki) in the San Juan Islands, Washington - Jamie Glasgow; Jennifer D. De Groot; Maureen P. Small (Conservation Genetics, 2020)
Understanding the conservation status of native fish populations is increasingly important because they are put at risk by mounting anthropogenic pressures, including climate change. Conventional approaches to assess fish populations can be logistically challenging and cost-prohibitive. As a result, resource managers often make assumptions about the status of fish populations based on limited information. The watersheds of Washington’s San Juan Islands were considered too small to support wild salmonid populations. Many streams flow only seasonally, and all have been subjected to varying degrees of anthropogenic impacts affecting their ecological integrity. Nonetheless, we found that at least five watersheds in the archipelago support populations of coastal cutthroat trout ( Oncorhynchus clarki clarki ). To better understand the conservation status of coastal cutthroat trout populations there, we genotyped approximately fifty trout in each of three watersheds: Cascade and Doe Bay creeks on Orcas Island and Garrison Creek on San Juan Island. Results suggest that two watersheds support native populations and one supports naturalized hatchery fish. The likely native coastal cutthroat trout diversity documented in the two watersheds contributes to the overall diversity of the species, demonstrates that species’ resiliency, and provides justification for conservation measures. Effective management and conservation planning in data-limited situations requires the use of a precautionary approach. Population genetics provide a useful tool for identifying vulnerable fish populations and understanding their relationships with other conspecific populations. This information can inform restoration goals and help identify and prioritize restoration and protection measures.